The food situation and Suan Dusit University’s dominant identity: A scenario of School of Culinary Arts development - Pholpuntin, Sirote; Moungprasert, Suwamarn; Sriboonrawd, Jiyaporn; Tungdamnernsawad, Supaporn (Journal of Thai Food Culture, 2023)
This academic article presents the food situation and Suan Dusit University’s dominant identity: a case study of the School of Culinary Arts development scenario. When the whole of Suan Dusit University has become a learning source, the university is prompt to leap toward the future. With the university’s home economics past as a dominant identity that builds ‘our authentic selves’, history is an essential supporting pillar for future development since ‘culinary’ is both an art of service and science. As a result, students can learn raw materials, tools, and hands-on cooking to cook food following standards. Suan Dusit University is the only educational institution that produces graduates to become hands-on practitioners. A scenario of the School of Culinary Arts development has to relate to the university’s future budgets to support the school, for example, a food processing factory, butter factory, cheese factory, food laboratory, One World Library, and cocktail mixer ingredient library. Therefore, instructors must plan well to contribute to students’ cooking competencies and teach them how to ‘learn.’ Curriculum and teaching development must consider history, and we must compete in parts that we can win.